Outsourcing Responsibility. - Neville-Neil, George V. (Communications of the ACM, 2014)
The article offers the author's advice for outsourcing responsibility and handling a failed debugger. He mentions the dependence of people on codes which cannot be read due to its binary form in a software system which is designed from other parts. He notes the aspects of program trustworthiness along with the stability of application programming interfaces (APIs). He also points out the imperfection of written programming tools as well as the concealment of timing bugs by print statements that leads to deception.